2020
DOI: 10.21203/rs.3.rs-59497/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Doc’EDS: A French Semantic Search Tool to Query Health Documents from A Clinical Data Warehouse

Abstract: Background: Unstructured data from electronic health record is a gold mine. Doc’EDS is a pre-screening tool based on textual and semantic analysis. The system provides an easy-to-use interface to search documents in French. The aim of this study is to present the tools and to provide a formal evaluation of its semantic features. Material & Methods: Doc’EDS is a search tool built on the top of the clinical data warehouse developed in the Rouen University Hospital. This tool is a multilevel search engine com… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In these cases, the automatic processing of clinical narrative is used. It combines several NLP algorithms to ensure that searched keywords are relevant (i.e., not in a negative sentence for example) or present in text specific segments (such as conclusion for example) even if those documents are natively unstructured [15].…”
Section: Entrepôt De Santé Normand (Edsan)mentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, the automatic processing of clinical narrative is used. It combines several NLP algorithms to ensure that searched keywords are relevant (i.e., not in a negative sentence for example) or present in text specific segments (such as conclusion for example) even if those documents are natively unstructured [15].…”
Section: Entrepôt De Santé Normand (Edsan)mentioning
confidence: 99%
“…Processing CN with NLP is never perfect: some false positives or false negatives can occur (e.g., in detection of negations) [15]. Thus, an evaluation should be conducted to measure the precision of each query.…”
Section: Limitsmentioning
confidence: 99%
“…In this paper, we use a unique prescription dataset from the Rouen University Hospital data warehouse (7) to test the impact of different contextual items on the DDI frequency measurement.…”
Section: Introductionmentioning
confidence: 99%
“…In Rouen, patients were included from the Clinical Dataware House (EDSaN) with a cross-search using the keywords in narrative documents: 'allergic tests' and 'immunosuppressive therapy' (list of drug commercial names or substances). 1 ST were performed in the same way in the two centres according to the international guidelines. 2,3 All included patients (n = 61) gave written consent for allergological investigations and were informed of the potential use of the data for research purposes.…”
mentioning
confidence: 99%
“…6 We assume that the heterogeneity of our real-life population (type of IT and culprit drugs, Accuracy of commercially available smartphone applications for the detection of melanoma DOI: 10.1111/bjd.20903 DEAR EDITOR, Artificial intelligence (AI) has shown promise in the analysis of images for detection of melanoma. 1 The number of available dermatology smartphone applications ('apps') is rapidly growing and there is increasing interest in apps that provide diagnosis or triage of skin lesions. 2,3 A 2020 systematic review found that nine studies evaluating six apps had poor study design and high risk of bias.…”
mentioning
confidence: 99%